Key themes in Zechariah 1-8 - O'Kennedy, Daniël Francois 1964- (2019)
The discussion of key themes or the message of Zechariah 1-8 is neglected in commentaries that were published during the past five years. This article focuses on this neglected part of Zechariah research and investigates the following key themes: YHWH's divine presence and the rebuilding of the temple in Zion; The lordship and sovereignty of YHWH; Sin and punishment/judgment; Turn to YHWH (repentance) and obedience; YHWH's return, grace, love and forgiveness; Realized eschatology and future hope; Israel and the nations; and Leadership. One cannot really say that there are any unique themes in Zechariah 1-8 or that the author/s had one central theme in mind. There are many similarities with other books in the OT, especially the post-exilic prophetic books. However, we must acknowledge that Zechariah 1-8 places more emphasis on certain themes and discusses them in a unique way.
Keywords: Bibel